Dairy consumption in northern Nigeria: Implications for development policies - Jansen, G.P. (Elsevier, 1992)
Data from a household survey were used to investigate levels and patterns of dairy product consumption in northern Nigeria. The data were sorted by income category, ethnic group and geographic location. Dairy products were grouped into traditional and imported products. Per capita consumption averaged double that for sub-Saharan Africa. Consumption differed significantly between rural and urban households and between ethnic groups. Consumers' preferences for traditional dairy products and past experiences with high-input, large-scale dairy production justify increased support for the development of traditional milk production systems and per urban dairy production and processing.